Patterns of Recurrence following Inguinal Lymph Node Dissection for Penile Cancer: Optimizing Surveillance Strategies. Issue 4 (25th October 2021) - Chakiryan, Nicholas H.; Dahmen, Aaron; Bandini, Marco; Pederzoli, Filippo; Marandino, Laura; Albersen, Maarten; Roussel, Eduard; Zhu, Yao; Ye, Ding-Wei; Ornellas, Antonio A.; Catanzaro, Mario; Hakenberg, Oliver W.; et al.
Abstract : Purpose: Our primary objective is to detail the incidence, site, and timing of penile squamous cell carcinoma (pSCC) recurrence after inguinal lymph node dissection (ILND). Materials and Methods: We performed a retrospective analysis of 551 patients who underwent ILND for pSCC from 2000 to 2017. The primary outcome was pSCC recurrence after ILND. Recurrences were identified and stratified by site. Timing of recurrence was determined. Multivariable logistic regression analysis determined associations with recurrence. Multivariable Cox regression analysis determined associations with overall survival (OS). Sub-group analysis of the distant recurrences analyzed timing and OS by site of distant recurrence. Results: After ILND pSCC recurred in 176 (31.9%) patients. Median time to recurrence was 10 months for distant recurrences, 12 for inguinal, 10.5 for pelvic, and 44.5 for local. Greater than 95% of distant, inguinal, and pelvic recurrences occurred within 48 months of ILND, versus 127 months for local recurrences. Post-ILND recurrence was associated with pN2 (OR 1.99, 95% CI 1.0–4.1), and pN3 (OR 7.2, 95% CI 4.0–13.7). Patients who had local recurrence had similar OS to those without (HR 1.5, 95% CI 0.6–3.8), and worse OS was identified in patients with inguinal (HR 4.5, 95% CI 2.8–7.1), pelvic (HR 2.6, 95% CI 1.5–4.5), or distant (HR 4.0, 95% CI 2.7–5.8) recurrences. Patients with lung recurrences had worse OS than other sites (HR 2.2, 95% CI 1.1–4.3). Conclusions: Of the patients 31.9% had post-ILND recurrence associated with high pN staging. Greater than 95% of distant, inguinal, and pelvic recurrences occurred within 48 months, suggesting surveillance beyond this is low yield. Local recurrences occurred over a longer timeline, emphasizing necessity of long-term surveillance of the primary site.